Preclinical efficacy of oncolytic VSV-IFNβ in treating cancer: A systematic review - Moglan, Abdulaziz Molham; Albaradie, Omar A.; Alsayegh, Fares Fayez; Alharbi, Hussam Mohsen; Samman, Yahya Marwan; Jalal, Mohammed M.; Saeedi, Nizar H.; Mahmoud, Ahmad Bakur; Alkayyal, Almohanad A. (Frontiers in Immunology, 2023)
Background: Cancer incidence and mortality are increasing rapidly worldwide, necessitating further investigation into developing and optimizing emergent cancer therapies. Oncolytic viruses such as vesicular stomatitis virus encoding interferon β (VSV-IFNβ) have attracted considerable attention, as they offer great efficacy and safety profiles. This systematic review aimed to determine and compare the efficacy profile between VSV-IFNβ and non-treatment controls in preclinical cancer models. Methods: The Embase and Medline databases were systematically searched for relevant studies using related key terms and Medical Subject Headings (MeSH). Titles, abstracts, and full texts were screened, and data from eligible articles were extracted by two groups independently and in duplicate (two reviewers per group). Disagreements were resolved by a fifth independent reviewer. The included articles were all preclinical (translational) in vivo English studies that investigated and compared the efficacy profile between VSV-IFNβ and non-treatment controls in animal models. The risk of bias among the studies was assessed by two reviewers independently and in duplicate using SYRCLE’s risk-of-bias tool for animal studies; disparities were addressed by a third independent reviewer. Results: After employing relevant MeSH and key terms, we identified 1598 articles. A total of 87 articles were either duplicates or conference proceedings and were thus excluded. Following title and abstract screening, 37 articles were included in the full-text assessment. Finally, 14 studies met the eligibility criteria. Forty experiments from the included studies examined the potential efficacy of VSV-IFNβ through different routes of administration, including intratumoral, locoregional, and intravenous routes. Thirty-five experiments reported positive outcomes. Meanwhile, five experiments reported negative outcomes, four and one of which examined intratumoral and intravenous VSV-IFNβ administration, respectively. Conclusion: Although the majority of the included studies support the promising potential of VSV-IFNβ as an oncolytic virus, further research is necessary to ensure a safe and efficacious profile to translate its application into clinical trials.